Active Learning and Reinforcement Learning for Autonomous Catalyst Design in CO2 Hydrogenation - Chen, Yingru (International Journal of Materials Science and Technology Studies, 2024)
The increasing concentration of carbon dioxide (CO2) in the atmosphere presents a significant challenge in the context of climate change, necessitating innovative strategies for greenhouse gas mitigation. CO2 hydrogenation, which converts CO2 into hydrocarbons and other valuable chemicals using hydrogen, has emerged as a promising method for addressing both carbon emissions and renewable energy production. Catalysts are crucial in enhancing the efficiency and selectivity of these reactions; however, traditional catalyst design methods often rely on laborious trial-and-error approaches, which can be inefficient and resource-intensive. This paper explores the integration of active learning and reinforcement learning as advanced methodologies for automating catalyst design specifically for CO2 hydrogenation. Active learning focuses on selecting the most informative data points to improve model predictions while minimizing experimental costs, whereas reinforcement learning optimizes decision-making processes through iterative feedback. A case study demonstrates the application of these techniques, leading to the successful identification of novel catalyst compositions that exhibit superior performance metrics. The findings highlight the potential of machine learning to revolutionize catalyst discovery, ultimately contributing to more sustainable CO2 conversion strategies.